2018
DOI: 10.1097/hco.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of persistent atrial fibrillation and beyond

Abstract: Purpose of reviewPercutaneous catheter ablation is an effective treatment for atrial fibrillation. However, catheter ablation for the treatment of persistent atrial fibrillation or long-standing persistent atrial fibrillation is associated with unsatisfying success rates. This review aims to summarize the recent literature on the progress of catheter ablation among patients with persistent atrial fibrillation Recent findingsIn this review, we outline the potential future therapeutic techniques of catheter abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…2 For the unstable and chaotic properties of complex AF signals, phase mapping could provide spatial and temporal information that helps to reveal the electrical properties of the atrial matrix, and offering additional insight into AF mechanisms. 6 Using a novel electrogram similarity analysis and real-time phase mapping to identify the rotors/drivers, we have previously reported, from a randomized trial of patients with persistent AF, a lower AF recurrence rate using adjuvant rotor/ driver ablation when compared with CFAE ablation, after PVI. 7 This finding suggested that additional ablation for the rotors/drivers after PVI guided by nonlinear phase maps improves the SR outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 For the unstable and chaotic properties of complex AF signals, phase mapping could provide spatial and temporal information that helps to reveal the electrical properties of the atrial matrix, and offering additional insight into AF mechanisms. 6 Using a novel electrogram similarity analysis and real-time phase mapping to identify the rotors/drivers, we have previously reported, from a randomized trial of patients with persistent AF, a lower AF recurrence rate using adjuvant rotor/ driver ablation when compared with CFAE ablation, after PVI. 7 This finding suggested that additional ablation for the rotors/drivers after PVI guided by nonlinear phase maps improves the SR outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In the STAR AF 2 trial, the lack of benefits in maintaining sinus rhythm (SR) with either additional linear or CFAE ablation compared to PVI only raised the concern that additional ablation after PVI might not be feasible in patients with persistent AF 2 . For the unstable and chaotic properties of complex AF signals, phase mapping could provide spatial and temporal information that helps to reveal the electrical properties of the atrial matrix, and offering additional insight into AF mechanisms 6 . Using a novel electrogram similarity analysis and real‐time phase mapping to identify the rotors/drivers, we have previously reported, from a randomized trial of patients with persistent AF, a lower AF recurrence rate using adjuvant rotor/driver ablation when compared with CFAE ablation, after PVI 7 .…”
Section: Introductionmentioning
confidence: 99%